Cost–benefit analysis of an enhanced recovery protocol for pancreaticoduodenectomy. Issue 13 (22nd October 2015) - Joliat, G -R; Labgaa, I; Petermann, D; Hübner, M; Griesser, A -C; Demartines, N; Schäfer, M
Abstract: Background: Enhanced recovery after surgery (ERAS) programmes have been shown to decrease complications and hospital stay. The cost-effectiveness of such programmes has been demonstrated for colorectal surgery. This study aimed to assess the economic outcomes of a standard ERAS programme for pancreaticoduodenectomy. Methods: ERAS for pancreaticoduodenectomy was implemented in October 2012. All consecutive patients who underwent pancreaticoduodenectomy until October 2014 were recorded. This group was compared in terms of costs with a cohort of consecutive patients who underwent pancreaticoduodenectomy between January 2010 and October 2012, before ERAS implementation. Preoperative, intraoperative and postoperative real costs were collected for each patient via the hospital administration. A bootstrap independent t test was used for comparison. ERAS-specific costs were integrated into the model. Results: The groups were well matched in terms of demographic and surgical details. The overall complication rate was 68 per cent (50 of 74 patients) and 82 per cent (71 of 87 patients) in the ERAS and pre-ERAS groups respectively ( P = 0·046). Median hospital stay was lower in the ERAS group (15 versus 19 days; P = 0·029). ERAS-specific costs were €922 per patient. Mean total costs were €56 083 per patient in the ERAS group and €63 821 per patient in the pre-ERAS group ( P = 0·273). The mean intensive care unit (ICU) and intermediate care costs were €9139 and €13 793 per patient for the ERAS and pre-ERAS groups respectively ( P = 0·151). Conclusion: ERAS implementation for pancreaticoduodenectomy did not increase the costs in this cohort. Savings were noted in anaesthesia/operating room, medication and laboratory costs. Fewer patients in the ERAS group required an ICU stay. Abstract : Some savings